Franco Cordero e il processo accusatorio - Ferrua, Paolo (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
Today, there is an unbridgeable gap between the principles contained in Article 111 of the Constitution, which is based on the accusatory model, and the criminal trial in law, and in jurisprudence and practice. The reasons for this are complex. They include: the hostility of a large part of the judiciary towards the adversarial rule; the fear that the accusatory model is a prelude to the separation of careers; the jurisprudence that often leads to a reductionist interpretation of procedural guarantees; and artificial intelligence, some aspects of which risk depriving the judge and the parties of their irreplaceable commitment.